2015
DOI: 10.1111/tpj.12747
|View full text |Cite
|
Sign up to set email alerts
|

The response of Chlamydomonas reinhardtii to nitrogen deprivation: a systems biology analysis

Abstract: SUMMARYDrastic alteration in macronutrients causes large changes in gene expression in the photosynthetic unicellular alga Chlamydomonas reinhardtii. Preliminary data suggested that cells follow a biphasic response to this change hinging on the initiation of lipid accumulation, and we hypothesized that drastic repatterning of metabolism also followed this biphasic modality. To test this hypothesis, transcriptomic, proteomic, and metabolite changes that occur under nitrogen (N) deprivation were analyzed. Eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
241
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(272 citation statements)
references
References 42 publications
23
241
0
8
Order By: Relevance
“…The false-positive rate of protein identification was assessed with an automatic decoy database search, and identified proteins were grouped based on 98% homology with Scaffold version 3.1 (Proteome Software). Full details can be found in Park et al (2014).…”
Section: Proteomicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The false-positive rate of protein identification was assessed with an automatic decoy database search, and identified proteins were grouped based on 98% homology with Scaffold version 3.1 (Proteome Software). Full details can be found in Park et al (2014).…”
Section: Proteomicsmentioning
confidence: 99%
“…reinhardtii samples were harvested at 0, 0.5, 1, 2, 4, 6, 12, and 24 h after N deprivation, and transcripts were analyzed by high-throughput sequencing as described by Park et al (2014). Nitrogen-replete cells (time 0) were used as the reference for all subsequent time points.…”
Section: Changes In the Levels Of Transcripts And Proteins Of Photosymentioning
confidence: 99%
See 1 more Smart Citation
“…wild-type, and C1 lines were estimated by the DESeq algorithm with a q-value cutoff of less than 0.05 from RNA sequencing (RNA-seq) data (Supplemental Table S1; Supplemental Data Set S1). For RNA-seq analysis, RNA was extract from each line 6 h after being transferred to Tris-acetate phosphate medium without a nitrogen source (TAP 2 N; normal TAP medium as a control), because the previous reports revealed that TAG accumulation starts in the cells (Park et al, 2015); expression of a large part of conserved N-regulated genes has already responded (Schmollinger et al, 2014) at that time point. Consequently, the expression levels of 937, 509, and 405 genes were increased significantly in N-deficient conditions in tar1-1, wild-type, and C1 cells, respectively (Fig.…”
Section: Differentially Expressed Genes In the Tar1-1 Mutant In N-defmentioning
confidence: 99%
“…G6PDH is the first step in the pentose phosphate pathway that regenerates NADPH for anabolic metabolism, as well as pentoses like ribose-5 phosphate, a precursor in the synthesis of nucleotides. When increased, the level of enzymes involved in oxidative pentose phosphate pathway (e.g., G6PDH and 6-P gluconate dehydrogenase), rather than leading to the accumulation of carbon skeletons for cellular growth, regenerates NADPH, essential for the reduction in fatty acid biosynthesis [34].…”
Section: Shifts In Metabolites and Enzyme Activities After Bleachingmentioning
confidence: 99%